Teaching the literature review: A practical approach for college instructors - Cisco, Jonathan (Teaching and Learning Inquiry, 2014)
Instructors across the disciplines require their students to write literature reviews. Although numerous sources describe the literature review process, instructors and students face difficulty when approaching the structure of a literature review. This paper presents a straightforward, efficient approach for teaching students how to write a literature review. Developed over the course of three years at a university writing center, this lesson received substantial support from students across the disciplines. This paper reflects on one group of students’ experiences while writing literature reviews in a political science course, showing that students demonstrated a sense of confidence and direction after the lesson. University professors, writing center staff, and content-discipline instructors in higher education classrooms can alleviate their students’ anxiety about literature reviews by using this lesson in their classrooms.